UV-Visible Spectroscopic Analysis of Influence of Trace Element Ions on Albendazole - UTHRA*, D.; ANITA, B.; SURIYA, B. (Asian Journal of Chemistry, 2009)
Prersent work aims to employ UV-Visible spectral analysis of an anthelmentic drug albendazole. This drug falls under the category of WHO's model list of essential drugs for the eradication of helminthiasis. The interaction of this drug with certain ions like sodium, calcium and potassium which are present in blood as trace elements has been studied with the aid of UV-Visible spectroscopy as a tool.